Global and country-specific movements in real effective exchange rates: Implications for external competitiveness. (September 2017) - Nagayasu, Jun
Highlights: Real effective exchange rates are decomposed into global and country-specific factors using the Bayesian factor model. The majority of exchange rate movements can be explained by country-specific factors. Real interest rates are also decomposed into global and country-specific factors. The global factor in exchange rates can be explained by the global interest rate. The country-specific factors in exchange rates can be explained by those in interest rates. Abstract: Using the Bayesian factor model, we decompose real effective exchange rates, which are considered a measure of external competitiveness, into global and country-specific factors. Among several findings, we report a particular global trend in real exchange rates, but a substantial proportion of their variation is found to be country-specific. In line with this finding, we find that structural shifts, when they do exist, are contained in country-specific factors. Furthermore, consistent with economic theory, this global factor is closely related to a trend in the global interest rate, while country-specific factors are closely related to idiosyncratic movements in the countries' own interest rates. Such a decomposition results in better understanding of the exchange rate-interest rate relationship, and therefore our results can be interpreted as evidence that external competitiveness is heterogeneous among countries and that economic policies can influence countries' competitiveness.